An Ir3L2 complex with anion binding pockets: photocatalytic E–Z isomerization via molecular recognition. Issue 73 (27th August 2021) - Sunohara, Haruka; Koyamada, Kenta; Takezawa, Hiroki; Fujita, Makoto
Abstract : A photoactive Ir3 L2 complex with anion recognition pockets was synthesized by self-assembly. The complex selectively activated an anionic styrene derivative toward E – Z isomerization. Abstract : A molecular host with photosensitizing centers provides photo-responsive host–guest properties based on its molecular recognition ability. Here, we construct a self-assembled photoactive Ir(iii ) cage-shaped complex that contains anion binding pockets on its rim. The anion recognition ability of the complex enables efficient catalysis of the visible-light-induced E – Z isomerization of an anionic styrene derivative.